2010
DOI: 10.5468/kjog.2010.53.11.988
|View full text |Cite
|
Sign up to set email alerts
|

The effect of balanced incline shoes on walking and feet for the pregnant women

Abstract: Objective: This study investigated the effects of the balanced incline shoes on the stabilized walking, fatigue reduction, improvement of blood circulation and prevention of foot related disease for the pregnant women. Methods: The seven 7~9 month pregnant women and three maternities within 3 months after delivery without a history of disease performed the cycles for each of the two walking conditions: wearing balanced incline shoes and flat shoes. The differences between the two walking conditions were statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In contrast to the decreased PSV found in the control group, significant increases in peak systolic velocity were observed in women in the experimental group who were provided with the special footwear, especially between the first and second measurements. A similar effect on the venous blood flow was observed in pregnant women wearing balanced inclined shoes in a previous study by Jang et al 10 In a study by Sousa et al, 19 who was testing unstable shoes on non-pregnant subjects, an increase in popliteal vein blood flow velocity was found in participants wearing the footwear tested. The increase in venous return in participants wearing the unstable shoes was associated with the increased gastrocnemius muscle activity in their study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast to the decreased PSV found in the control group, significant increases in peak systolic velocity were observed in women in the experimental group who were provided with the special footwear, especially between the first and second measurements. A similar effect on the venous blood flow was observed in pregnant women wearing balanced inclined shoes in a previous study by Jang et al 10 In a study by Sousa et al, 19 who was testing unstable shoes on non-pregnant subjects, an increase in popliteal vein blood flow velocity was found in participants wearing the footwear tested. The increase in venous return in participants wearing the unstable shoes was associated with the increased gastrocnemius muscle activity in their study.…”
Section: Discussionsupporting
confidence: 79%
“…For example, balanced inclined shoes were observed to decrease plantar pressure moments and increase bloodstream velocity, suggesting that this type of footwear may both decrease the excessive load on the feet and improve the blood circulation of feet during pregnancy. 10 The patented footwear and insoles (J Hanák R, Ltd.) used in this study are designed to help redistribute the forces acting on the foot, to support both longitudinal and transverse arches of the foot, and to strengthen the foot muscles during movement and, furthermore, they are claimed to have a positive effect on foot blood supply. 11 Therefore, the purpose of this study is to evaluate the effects of this special footwear on changes in blood flow velocity and the cross-sectional area of the popliteal vein at 25, 30, and 35 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these results, a study by Lim et al 14 ) reported that hemiplegic patients who performed trunk stabilization exercises for 8 weeks showed a significant increase in pressure on the hindfoot. In addition, Jang et al 15 ) reported that balanced incline shoes decreased foot pressure by 15% compared to flat shoes, thereby reducing loads on the feet, ankles, and knees by distributing pressure to the outside of the feet. The present study, too, found an increase in pressure on the outside of the feet, resulting in a positive effect on the body.…”
Section: Discussionmentioning
confidence: 99%
“…heir results show, that special footwear contributes to a decrease of the excessive load on the feet measured by plantar pressure and an improvement of the foot blood circulation (Jang et al, 2010;Marques et al, 2005); however, the number of studies of their efect on the lower limb alignment during the gait is lacking. In this study the efect of the tested footwear was ob-served in the experimental group by verticalization in the sagittal plane of pelvis position during the heel contact with the loor.…”
Section: Discussionmentioning
confidence: 99%